The role of artificial intelligence in education among college instructors: Palestine Technical University Kadoorie as a case study - Reham Salhab (Frontiers in Education)
IntroductionThis study aims to investigate AI potentials, ethical use, and challenges at PTUK.MethodsA mixed approach is utilized in this study to examine the perceptions of college instructors from different disciplines. A pre-existing scale of attitudes toward the ethics of artificial intelligence (AT-EAI) was used to assess the attitudes of 88 college instructor towards ethical use of AI. A phenomenological approach as well was conducted to gather information for the qualitative data. Semi-structured interviews with 17 participants were performed with college instructors who use AI in their teaching. One sample t-test was utilized to investigate the attitudes towards ethical use.ResultsResults revealed that justice, transparency, determination and no maleficence, and responsibility are statistically significant at a moderate level. Privacy was found at a moderate degree. Qualitative analysis yielded three themes for potential: academic productivity, accessibility, and multimodal teaching. Three themes for challenges: Ai quality services, lack of interaction, and need for teaching philosophy adaptation.DiscussionThe researcher recommendsthat further research and collaboration are necessary to maximize the benefits of AI in education and ensure its seamless integration into teaching practices.